Unusual case of polyarthritis and hepatorenal syndrome associated with Leptospira interrogans infection in a dog: A case report. (January 2021) - Paz, Lucas Nogueira; Dias, Carla Silva; Carvalho, Vitor Moraes Pina de; Muramoto, Caterina; Estrela-Lima, Alessandra; Pinna, Melissa Hanzen
Abstract: Leptospirosis is a zoonotic disease caused by spirochetal bacterial of the genus Leptospira affecting virtually all mammals. The infection has a broad range of effects, from mild clinical manifestation to multiple organ failure, and ultimately death. A 5-months-old male unvaccinated dog was admitted to the University Veterinary Teaching Hospital presenting dullness, dehydration, jaundiced mucous, bloody diarrhea, vomiting, and hyporexia. Microscopic agglutination test (MAT) detected serological titers of 1:1.600 for serogroup Canicola. After five days of monitoring by the medical team he developed fever and swelling of carpal and tarsal joints, accompanied by functional limitation. Initial antimicrobial treatment was instituted for leptospirosis. Polyarthritis responsiveness to glucocorticoid therapy was observed through decreasing signs of inflammation of the affected joints. The diagnosis of leptospirosis was further confirmed by molecular investigation for Leptospira spp. on blood and synovial fluid samples. Amplification and sequencing of the secY partial gene characterized the infective bacterial as Leptospira interrogans . From the 7th day the respiratory condition worsened and on Day 14 the patient evolved to death, when necropsy and histological evaluation were performed. Prominent anatomopathological findings included: fibrinous polyarthritis, bronchointerstitial pneumonia, intense hepatocyte dissociation, cholestasis, and periportal multifocal hepatitis, diffuse acute tubular necrosis, and significant dystrophic mineralization in the renal parenchyma, lungs, and atrial endocardium. Here, we present a case report of systemic clinical manifestations polyarthritis associated with the presence of leptospiras in the synovial fluid. We highlight the need for richer knowledge about the different clinical manifestations of leptospirosis. Highlights: Leptospirosis-associated polyarthritis in a dog. Leptospiral DNA in arthritic canine. Septal and bronchiolar epithelium mineralization. Molecular characterization of Leptospira interrogans in synovial fluid samples of a dog.